(untitled) (VITAE Academia Biomédica Digital, 2004)
The purpose of this study was to evaluate the effect of verapamil administration on Human Fetuses in High Risk Pregnancies (FHRP) by Proton Magnetic Resonance Spectroscopy (1HMRS) after Lactate identification. Two 1HMRS studies were performed on a 1.5 Tesla system using the body RF coil: the first one was done between 30-31 weeks of gestation and the second between 34-35 weeks after verapamil administration. The results obtained in the second 1HMRS study show a significant decrease in Lactate signal in FHRP compared with the first study. This reduction could be related to a more oxygen availability due to the verapamil vasodilator effect in FHRP.